2022
DOI: 10.1155/2022/7454982
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Ant Colony Algorithm‐Based Audit Supervision to Promote the Optimization of New Infrastructure Investment Environment

Abstract: Infrastructure investment has the characteristics of high start-up cost, high initial cost, long cycle, slow recovery, high risk, and high public welfare. Maintenance after completion requires stable financial support, maintenance costs are easily affected by government agencies, and investment efficiency is significantly reduced. This article focuses on the ant colony algorithm audit and supervision to promote the optimization of the new infrastructure investment environment and understands the relevant theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…According to the theory of ACO [8][9][10], traversing through this process, the best route will converge since the ant descendants will tend to move on the paths that contain more pheromones.…”
Section: Incorporating Aco With the Robotmentioning
confidence: 99%
“…According to the theory of ACO [8][9][10], traversing through this process, the best route will converge since the ant descendants will tend to move on the paths that contain more pheromones.…”
Section: Incorporating Aco With the Robotmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%